Sistematični pregled dejavnikov učinkovitosti računalniškega kognitivnega treninga pri otrocih z motnjo pozornosti s hiperaktivnostjo - Mičič, Sara (Psihološka obzorja (Ljubljana), 2021)
Computerized cognitive training (CCT) paradigms for children with attention defi cit hyperactivity disorder (ADHD) are designed to overcome specifi c defi cits and reduce symptoms of the disorder. Such training is increasingly being researched, but it is not entirely clear how it aff ects generalised functional defi cits, such as attention defi cit, impulsivity, lack of behavioural inhibition, planning, and organisation. Executive functions defi cits, which include working memory defi cits, make up a large part of ADHD and may be the basis for other symptoms of the disorder, such as attention impairment, lack of motivation, hyperactivity, and conduct problems. Therefore, many studies on training executive functions and working memory assume that improving these functions can reduce ADHD symptoms. The purpose of this paper is to review and critically evaluate research in the area of CCT for children with ADHD and determine whether CCT has shown promising results in overcoming ADHD-related defi cits in previous studies and what type of CCT is most promising. The articles included in this systematic review were found through databases in EBSCOhost, Science Direct, and Web of Science. Studies showed that CCT has the potential to improve cognitive functions in children with ADHD. Some studies also showed a reduction in dysfunctional and impulsive behaviours. However, the studies are not congruent regarding the CCT eff ects on these symptoms and they also diff er in the type of CCT used.
Keywords: attention deficit; children; children with mild intellectual disability; computerized cognitive training; delovni spomin; executive functions; hiperaktivnost; hyperactivity disorder; izvršilne funkcije; kognitivne sposobnosti; motnja pozornosti; otroci; otroci z lažjo motnjo v duševnem razvoju; računalniški kognitivni trening; working memory